A 360-deg Digital Image Correlation system for materials testing. (July 2016) - Genovese, K.; Cortese, L.; Rossi, M.; Amodio, D.
Abstract: The increasing research interest toward natural and advanced engineered materials demands new experimental protocols capable of retrieving highly dense sets of experimental data on the full-surface of samples under multiple loading conditions. Such information, in fact, would allow to capture the possible heterogeneity and anisotropy of the material by using up-to-date inverse characterization methods. Although the development of object-specific test protocols could represent the optimal choice to address this need, it is unquestionable that universal testing machines (UTM) remain the most widespread and versatile option to test materials and components in both academic and industrial contexts. A major limitation of performing standard material tests with UTM, however, consists in the scarce information obtainable with the commonly associated sensors since they provide only global (LVDTs, extensometers, 2D-video analyzers) or local (strain gages) measures of displacement and strain. This paper presents a 3D Digital Image Correlation (DIC) system developed to perform highly accurate full-surface 360-deg measurements on either standard or custom-shaped samples under complex loading within universal testing machines. To this aim, a low cost and easy to setup video rig was specifically designed to overcome the practical limitations entailed with the integration of a multi-camera system within an already existing loading frame. In particular, the proposed system features a single SLR digital camera moved through multiple positions around the specimen by means of a large rotation stage. A proper calibration and data-processing procedure allows to automatically merge the experimental data obtained from the multiple views with an accuracy of 10 − 2 m m . The results of a full benchmarking of the metrological performances of the system are here reported and discussed together with illustrative examples of full-360-deg shape and deformation measurements on a Grade X65 steel sample under tensile loading. The methodology demonstrated to be robust and accurate thus representing a viable practical solution to afford the modern challenges in the field of materials and components testing. Highlights: We developed a DIC system for 360-deg measurements within universal testing machines. The system overcomes the limitations entailed with the use of a multiple camera system. The proposed method allows to capture the strain heterogeneity on the full surface of the sample. The benchmarking of the metrological performances proved the accuracy and robustness of the method. The full-surface experimental data can be used for inverse mechanical characterization.